INVESTIGATION ON THERMAL STABILITY AND PURITY DETERMINATION OF TWO ANTIHYPERTENSIVE DRUGS, VALSARTAN AND LOSARTAN POTASSIUM - Ibrahim, Magda M. (International Journal of Current Pharmaceutical Research, 2015)
Objective: The thermal behavior of two antihypertensive drugs: Valsartan (VAL) and Losartan potassium (LOS) was investigated using different thermal techniques. These include thermogravimetry (TGA), derivative thermogravimetry (DTG) and differential scanning calorimetry (DSC). Methods: Thermogravimetric data obtained from first step of decomposition of valsartan and losartan allowed the determination of kinetic parameters such as activation energy (Ea), frequency factor (A), order of reaction (n) and enthalpy of decomposition (âˆ†H). The purity of valsartan and losartan were determined by differential scanning calorimetry. Results: The thermal degradation of losartan and valsartan was followed a first-order kinetic behavior and evaluation of the relative thermal stabilities showed that LOS is more thermally stable than VAL. The decomposition modes were investigated and the fragmentation pathway of losartan was taken as example, to correlate the thermal decomposition with mass spectrometry. The purity of valsartan and losartan determined by differential scanning calorimetry was found to be 99.84 % and 99. 91 %, respectively, which was in good agreement with the pharmacopoeial results. Conclusion: Thermal analysis justifies its application in quality control of pharmaceutical compounds due to its simplicity, sensitivity and low operational costs. Â 